Examining the Relationship between Online Social Capital and eHealth Literacy: Implications for Instagram Use for Chronic Disease Prevention among College Students. Issue 4 (4th July 2017) - Paige, Samantha R.; Stellefson, Michael; Chaney, Beth H.; Chaney, Don J.; Alber, Julia M.; Chappell, Chelsea; Barry, Adam E.
ABSTRACT: Background : College students actively seek online health information and use Instagram, an image- and video-based social networking website, to build social networks grounded in trust and behavioral norms (social capital), which have the potential to prevent chronic disease.Purpose : This study aimed to (1) examine how intensity of Instagram use moderates the relationship between eHealth Literacy and online social capital in college students and (2) discuss how Instagram can be used as a social awareness platform for chronic disease prevention among college students.Methods : Hierarchical regression analyses were conducted to analyze web-based survey data from a random sample of college students ( N = 327).Results : Online bridging social capital was associated with greater ehealth literacy ( P < .05) and intensity of Instagram use ( P < .001), when controlling for sociodemographic variables. The relationship between ehealth literacy and online bridging social capital was strongest among respondents with average-intensity ( P < .01) and high-intensity ( P < .01) Instagram use compared to low Instagram intensity.Discussion : High intensity of Instagram use may strengthen college students' low ehealth literacy, especially when interacting with heterogeneous connections with weaker ties.Translation to Health Education Practice : Health Education Specialists should continue to explore how college students' intensity of Instagram use can be strengthened to build bridging online social capital and ultimately prevent chronic disease.